The clinical impact of a positive family history of psychosis or mental illness in psychotic and non-psychotic mentally ill adolescents. Issue 3 (2nd September 2017) - Paruk, Saeeda; Jhazbhay, Khatija; Singh, Keshika; Sartorius, Benn; Burns, Jonathan K
Abstract : Background: A family history of psychosis is associated with negative clinical characteristics of psychosis. Aim: We aimed to determine the relationship between a family history (in first-degree relatives) of psychosis (FHP) or of any mental illness (FHM), and the clinical features (including cannabis use) of first episode early onset psychosis (EOP). Method: Forty-five adolescents with first episode EOP presenting to psychiatric services were assessed by clinical interview with the following tools: socio-demographic questionnaire, Positive and Negative Syndrome Scale (PANSS), Symptom Onset in Schizophrenia (SOS) inventory, and the World Health Organisation's (WHO) Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) for cannabis misuse. Forty-five gender and age matched controls with incident non-psychotic mental illness were recruited from the same clinical sites. Results: While there was evidence of trend associations, EOP adolescents and controls did not differ in terms of either FHP or FHM. However, adolescents with a non-psychotic mental illness (controls) were significantly more likely to have a family history of non-psychotic mental illness (EOP = 13%; controls = 47%, p = 0.001). In EOP adolescents, a positive FHP was associated with a significantly lower mean PANSS positive score ( p = 0.009), but not with other clinical features. Conclusion: FHP may be a diagnostic clue in adolescents and is not necessarily associated with negative clinical characteristics at disease onset in EOP. However, this requires further research.